La recepción de la obra de Federico García Lorca en Hungría - Katona, Eszter (Acta Hispanica, 2008)
In her essay, the author provides a thorough overview of the history of the reception of Federico García Lorca's poetry in Hungary. The 110th anniversary of Lorca's birth, commemorated this year, makes such surveys very timely. The author's aim is to examine Lorca's Hungarian presence from various perspectives. In the first phase of her recent investigations, she concentrated on presenting all the Hungarian translations and editions of Lorca's oeuvre. In the following, the Hungarian reception of Lorca's oueuvre is examined, based on essays and other writings of literary criticism of the era. The author also focuses on the different theatrical representations of Lorca's dramas in Hungary all over the 20th century, and the diverse articles and other press releases covering those. It is also important to mention that prior to the 1970s, there existed already a significant wave of investigations about the Spanish poet: Gábor Tolnai, László Péter, László András, János Benyhe and László Németh, amongst many, not only provided excellent translations of Lorca's poems but also carried out investigations of literary theory and history. Still, by the decade of the 1980s, the intensity of the academic and literary interest towards Lorca faded; the current anniversary provides both an occasion and a positive auspice for the continuation of this work.